2018
DOI: 10.1142/s2010135x18500200
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of structural, optical and electrical properties of CdSe incorporated polyvinyl pyrrolidone nanocomposite for memory devices

Abstract: The important enhancement in the structural, dielectric and optical properties of pure polymer and CdSe incorporated polyvinyl pyrrolidone has been reported in this paper. The surface morphology of CdSe/PVP nanocomposite film is studied by using scanning electron microscopy (SEM). The chemical composition of different elements has been reported using energy dispersive X-ray (EDX) spectrum. The structure of polymer nanocomposite is determined with the help of X-ray diffraction (XRD) spectrum and is observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…From this figure, it is observed that the α>10 4 cm -1 which means the indirect transition happens. The rise of α is related to a rise in light absorption [23]. The nanocomposites are said to have an indirect energy gap if the value of α is less than 10 4 cm -1 .…”
Section: Resultsmentioning
confidence: 99%
“…From this figure, it is observed that the α>10 4 cm -1 which means the indirect transition happens. The rise of α is related to a rise in light absorption [23]. The nanocomposites are said to have an indirect energy gap if the value of α is less than 10 4 cm -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The optical conductivity of blend rises with the increase in MnO2 NPs ratio and photon energy. The rise in optical conductivity as MnO2 NPs ratio increase due to reduce the energy gap [27][28]. [29,30].…”
Section: A D C Bmentioning
confidence: 99%
“…Due to their strong brightness and good quantum yield, cadmium selenide (CdSe) QDs are more widely used than other QD types. Due to its exceptional incident photon to carrier efficiency and enhanced photo physical, photochemical, and electrochemical capabilities, cadmium selenide (CdSe) has been chosen as the most promising choice for nanocomposite materials 10,11 .High-quality CdSe-based quantum dots are ideal fluorescent tag candidates for solar cells, single-electrode transistors, light-emitting diodes, laser materials, and biological imaging 1,12 . The distinct size dependence of quantum dots distinguishes them from all other bulk materials because of quantum confinement 13 .…”
Section: Introductionmentioning
confidence: 99%